PENGELOLAAN KELAS IBU HAMIL DALAM UPAYA MENINGKATKAN PEMANFAATAN BUKU KIA DI WILAYAH KERJA PUSKESMAS ASTAMBUL KABUPATEN BANJAR - Vonny Khresna Dewi; Tut Barkinah; Rita Kirana (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Analysis of the partner situation based on data from the South Kalimantan Provincial Health Office found that the highest number of maternal deaths in 2021 was Tanah Laut Regency with 17 people and Banjar Regency with 16 people, while in 2022 the highest number of maternal deaths was Banjar Regency with 19 people (Hemorrhage: 1, Hypertension: 9, Covid: 1, and others: 8) and Banjarmasin Municipality with 14 people (Hemorrhage: 5, Hypertension: 2, Heart: 2, and others: 5). The cause of maternal death was Hypertension in pregnancy (32.4%), Postpartum hemorrhage (20.3%) and the period of death occurred in the Postpartum Period (48 hours after birth) by 61.6%. The high number of maternal, infant and child deaths is partly due to the delay factor (referring, arriving, getting adequate help). Some areas still have low coverage of maternal and child health programs. One of the causes is the low knowledge of mothers and families and not optimal utilization of the MCH book. Identification of partner problems from the results of the study revealed that most mothers' knowledge of the contents of the MCH book was still lacking because they did not read the book (did not have a MCH book: 19.2%, Have MCH book - can't show: 40.4% and have MCH book-can show: 40,4%). Priority efforts in reducing MMR in 2015-2019 include increasing the utilization of the MCH Book and implementing classes for pregnant women. The objective of community service is to be able to manage pregnant women's classes in an effort to increase the utilization of the MCH Book in the Working Area of Puskesmas Astambul, Banjar Regency. The solution offered is to increase knowledge and skills through the utilization of the MCH Book in the implementation of Maternity Classes to improve Maternal and Child Health in the Astambul Puskesmas Working Area of Banjar Regency. The contribution of Puskesmas Partners is as mentors, licensors, supporters and implementers of monitoring and evaluation of the sustainability of the Community Service Program. Targeted Mandatory Outputs The targeted mandatory output is the publication of the Community Service Journal “Journal of Independent Service” Target TS: Submit T+1: Accepted. Additional output is the target community service video for the year concerned. mThe target achievement of community service is an increase in the knowledge and skills of pregnant women about the implementation of pregnant women's classes for monitoring maternal and child health to 100%, and an increase in the utilization of the MCH Book to 100%. The follow-up plan of this community service activity makes a commitment with, Astambul Health Center, and related institutions to be responsible for maintaining the sustainability of this community service activity